2018
DOI: 10.1155/2018/9209873
|View full text |Cite
|
Sign up to set email alerts
|

Untreated Congenital Hypothyroidism Mimicking Hirschsprung Disease: A Puzzling Case in a One-Year-Old Child

Abstract: Congenital hypothyroidism is a clinical emergency due to its potential risk of mental retardation. Constipation might be present in hypothyroid children. However, Hirschsprung disease is rarely associated with congenital hypothyroidism. Herein, a case of congenital hypothyroidism in a one-year-old child mimicking Hirschsprung disease is described. Adequate treatment with levothyroxine sodium tablets controlled intestinal dysmotility that mimicked congenital intestinal aganglionosis due to the critical influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Conclusive evidence that THs influence the migration of enteric nerves have not been reported. But cases of HSCR combined with CH be reported from time to time 23–25. A cross-sectional study of the association between CH and congenital defects also identified 2 cases of HSCR in 212 children 26.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusive evidence that THs influence the migration of enteric nerves have not been reported. But cases of HSCR combined with CH be reported from time to time 23–25. A cross-sectional study of the association between CH and congenital defects also identified 2 cases of HSCR in 212 children 26.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in this field have only reported the prevalence of this condition and have not assessed it in healthy neonates and neonates with congenital hypothyroidism. Tahan et al investigated the complications of congenital hypothyroidism in a longitudinal study and reported constipation as one of the complications of this disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that thyroid dysfunction can result in the reduced gut motility, digestion and elimination, and common borderlines with constipation. 10 Further, those with hypothyroidism may face abnormal nutritional habits, and an unusual lifestyle exposes them to changing defecation habits leading to constipation. Overall, as evidenced in the present study, 1.0% of patients with constipation might suffer from hypothyroidism, which is higher than the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…According to their judgment, considering different underlying profiles including age and children's growth status could potentially affect the real rate of constipation. In a study by Tahan et al, 10 constipation affected nearly 12% of children with congenital hypothyroidism, and the connecting chain between two phenomena included hypomotility and pseudo-obstruction. In this regard, it seems that hypothyroidism and Hirschsprung disease should be considered in the differential diagnosis of children suffering from severe constipation.…”
Section: Discussionmentioning
confidence: 99%